The challenge to providing stroke care and rehabilitation in Malawi - George L Chimatiro; Anthea J Rhoda (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Much research activity throughout the world has advanced on acute stroke care interventions, however, patients in low- and middle-income countries (LMICs) benefit less from stroke care practices due to continuing challenges. The aim of this study was to systematically explore stroke care provision challenges at the largest referral hospital in Malawi, from the perspectives of service providers, patients with stroke and their caregivers. # Methods A qualitative exploratory study with purposefully-selected participants explored challenges to stroke care from the perspectives of service providers, patients with stroke, and caregivers through focus-group discussions. Semi structured interviews were also conducted with physicians for patients with stroke. Thematic analysis was used to categorize the data. # Results Four key themes emerged: 1) lack of effective implementation of stroke care approaches due to lack of recognition and priority in critical care medicine, limited interprofessional contacts, communication disarray among providers, and lack of follow-up after discharge, particularly from rehabilitation professionals; 2) erratic and insufficient physiotherapy treatment due to limited referrals by physicians, limited visibility of physiotherapists in the hospital, and lack of proper service planning by physiotherapists; 3) Patient-mix challenges from intermingling patients with varying conditions, risking both physical harm and the development of nosocomial infections, and; 4) resource limitations from inadequate qualified service providers, limited medical supplies, unreliable equipment, and lack of warm bedding for patients. # Conclusions This study presented the challenges to stroke care provision, from structural, practice, and resource perspectives. There is a need to put in place context specific, and implementable care protocols to facilitate holistic care for patients with stroke. Economically possible structural needs for instance introduction of stroke-specific care wards in the referral hospitals could improve quality of stroke care services in Malawi.